2019
DOI: 10.2147/cia.s205019
|View full text |Cite
|
Sign up to set email alerts
|

<p>Physical activity programs for older people in the community receiving home care services: systematic review and meta-analysis</p>

Abstract: The proportion of older adults is increasing around the world and most wish to live in their home until they die. To achieve this, many will require services in the home to remain living independently. To maintain function (ie, strength, balance, and endurance), physical activity needs to be undertaken on a regular basis, and is essential as a person ages. Unfortunately, as people age there is a tendency to reduce activity levels, which often leads to loss of function and frailty, and the need for home care se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 41 publications
1
42
0
2
Order By: Relevance
“…The main reason is that people who go to day care facilities have better cognitive and physical functions than people in nursing homes. Furthermore, the sooner people maintain or initiate moderate to vigorous PA, the more likely they will age successfully, and the better quality of life these people will have when aging (1,3,5,6,8,10,13). Therefore, there should not only be general guidelines for the general population as generated by the WHO, but also general guidelines for nursing homes and day care facilities regarding the minimum amount of PA training per day or week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason is that people who go to day care facilities have better cognitive and physical functions than people in nursing homes. Furthermore, the sooner people maintain or initiate moderate to vigorous PA, the more likely they will age successfully, and the better quality of life these people will have when aging (1,3,5,6,8,10,13). Therefore, there should not only be general guidelines for the general population as generated by the WHO, but also general guidelines for nursing homes and day care facilities regarding the minimum amount of PA training per day or week.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there should not only be general guidelines for the general population as generated by the WHO, but also general guidelines for nursing homes and day care facilities regarding the minimum amount of PA training per day or week. Although the bene ts of PA in aged persons have already been well documented (3,13), using technology while exercising has the bene ts of gathering quantitative data related to physical progress, amount of PA, etc. This is also implemented in i-ACT as not only the time of the execution is stored, but also the amount of targets reached, and the amount of compensational movements (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research around structured exercise programmes has been completed in different groups of community-dwelling older people, however few studies have focused on the older population receiving formal home care. A recent systematic review of physical activity programmes for older people receiving home care identified few consistencies and recommended the need for more evidenced based trials investigating physical activity promotion programmes tailored for this group of older adults 16,17 .…”
Section: Jfsf 11mentioning
confidence: 99%
“…n the modern world, one of the most pressing topics is increasing life expectancy and the aging society. As people get older, they become less physically active, which often leads to loss of function and weakness, as well as the need for home care services (Burton et al, 2019). In Lithuania, there are 40.5% of adults who engage in physical activity for at least 30 minutes 5 days a week or more (Liuima & Valentienė, 2018).…”
mentioning
confidence: 99%